Implementation on stimulation, detection, and early intervention of child growth and development (sdidtk) program in puskesmas mojo, surabaya still emphasize on growth screening - Susanti, Dwi; Sustini, Florentina (Folia Medica Indonesiana, 2017)
It's Important to conduct child development screening regularly in primary health services, so child developmental delay cases can be detected and treated as early as possible. Child development screening program in Puskesmas should been carried out integrated with growth screening in Stimulation, Detection, and Early Intervention of Child Growth and Development (SDIDTK) Program. Aims of this study was to gathering informations about the implementation of child development screening activity conducted by Puskesmas Mojo. This was a cross sectional study with kualitatif method. Primary data taken from under 5 years old child's mothers, kindergarten teachers, cadres, and health staff of Puskesmas Mojo. Secondary data gotten from PWS KIA report of Puskesmas Mojo.Results of SDIDTK activities in Puskesmas Mojo according to PWS KIA report, achieve 88.1% in 2013 and 95.2% in 2014. Child development screening activities done infrequenly in Posyandu. Routine activities of Posyandu was growth/nutrition screening. Child development screening activities done by visiting kindergarten school every 6 month but not every child getting development screen, only those who suspicious have developmental delay because of minimum number of staff and aids. Results of SDIDTK activities in Puskesmas Mojo only represents child growth screening activities.